2020
DOI: 10.1212/wnl.0000000000009818
|View full text |Cite
|
Sign up to set email alerts
|

In vivo synaptic density loss is related to tau deposition in amnestic mild cognitive impairment

Abstract: ObjectiveTo investigate in vivo whether synaptic loss and neurofibrillary tangle load spatially overlap and correlate with clinical symptoms in patients with amnestic mild cognitive impairment (aMCI).MethodsIn this cross-sectional study, 10 patients with aMCI and 10 healthy controls underwent triple PET-MRI with 11C-UCB-J (synaptic vesicle protein 2A), 18F-MK-6240 (tau deposition), and 11C-Pittsburgh compound B (β-amyloid) and neuropsychological assessment. Gray matter atrophy was assessed by voxel-based morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 36 publications
4
54
0
Order By: Relevance
“…1). In line with a previous study from Vanhaute and others [21], the pattern of tau pathology was slightly more widespread and pronounced compared to the pattern of reduced synaptic density, which corresponds with a conceptual model that suggests tau to precede and potentially drive structural degeneration and loss of synaptic function [51].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…1). In line with a previous study from Vanhaute and others [21], the pattern of tau pathology was slightly more widespread and pronounced compared to the pattern of reduced synaptic density, which corresponds with a conceptual model that suggests tau to precede and potentially drive structural degeneration and loss of synaptic function [51].…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies in patients with AD have observed strongest reductions in SV2A radiotracer-binding in the hippocampus [17][18][19], a key region for structural synaptic degeneration in AD [20]. Furthermore, a recent PET study observed an association between decreased SV2A-binding and increased tau-binding in the medial temporal lobe in patients with amnestic mild cognitive impairment [21].…”
Section: Introductionmentioning
confidence: 99%
“…By comparing measures of WM connectivity obtained by dMRI (CC and Strength) to tau accumulation obtained by tau PET, the present study shows that tau accumulation is negatively correlated with structural connectivity in the early Braak stage regions. This is consistent with our recent finding that tau-related WM alterations were concentrated in early tau propagation pathways and results from postmortem studies that synaptic density loss is related to tau deposition in the spectrum of AD (Pooler et al, 2014;Vanhaute et al, 2020). When compared to neurocognitive tests, tau deposition and network metrics showed disparate patterns.…”
Section: Discussionsupporting
confidence: 91%
“…In a more recent [ 11 C]UCB-J study with a larger cohort of 34 AD and MCI patients, the significant loss of synaptic density measured by PET in the hippocampus and entorhinal cortex followed by parahippocampal cortex, amygdala, lateral temporal cortex, pre-frontal cortex, posterior cingulate cortex/precuneus, lateral parietal cortex, and pericentral cortex was found to be generally correlated with atrophy measured by structural MRI which is in line with autopsy reports, and was more significantly correlated with CDR-SB ( r = −0.54, P = 0.00003) and episodic memory ( r = 0.56, P = 0.00001) than in the smaller sample reported earlier (de Wilde et al, 2016 ; Chen et al, 2018 ; Mecca et al, 2020 ). The relationship between cognitive performances and medial temporal (especially hippocampus and parahippocampal gyrus) synaptic density loss in aMCI was strengthened by a mutually correlated regional tau accumulation, as was revealed by a multi-tracer PET study using [ 18 F]MK-6240 and [ 11 C]UCB-J (Vanhaute et al, 2020 ).…”
Section: Pet Tracers For Imaging Synaptic Densitymentioning
confidence: 91%